Being more satisfied with romantic relationship status is associated with increased mental wellbeing in people with experience of psychosis - White, Rebecca; Haddock, Gillian; Haarmans, Maria; Varese, Filippo (Frontiers in Psychiatry, 2023)
Aims: Romantic relationships represent one of the most salient sources of social support. In general population studies, they are associated with both physical and psychological benefits. Research suggests that for people with psychosis, romantic relationships may also have a positive impact on a range of outcomes, but the reasons for these associations are still unclear. This study aims to investigate whether satisfaction with romantic relationships status is associated with better wellbeing outcomes in people with experience of psychosis and explore three possible psychological mediators of this relationship.Method: Participants who had previously sought support for psychosis (n = 190) completed an online survey including measures of relationship status satisfaction (the Satisfaction with Relationship Scale) as well as measures of psychotic symptoms (the CAPE-42), general well-being (Short Warwick-Edinburgh Mental Wellbeing Scale) and several psychological variables relevant to the pathway between romantic relationships and well-being outcomes, namely loneliness, internalised stigma, self-esteem and attachment.Results: Fearful attachment and partner criticism were negatively associated with relationship status satisfaction. Having a partner was positively associated with relationship status satisfaction.Higher levels of relationship status satisfaction were associated with reduced lower psychotic symptoms and increased higher mental wellbeing. This relationship was mediated by loneliness, internalised stigma, and self-esteem.Mental health services should be mindful of the associations between romantic relationship satisfaction and wellbeing. Satisfying romantic relationships should be considered as potentially protective factors by mental health services. Service users with a fearful attachment style may particularly benefit from support in this area.